Teaching Doris Lessing at IIUM: Islamic perspectives on her thoughts on education, literature, racism and women’s rights - Hasan, Md. Mahmudul (2015)
In this paper, I intend to look at Doris Lessing’s thoughts on education, literature, racism and women’s rights and locate possible commonalities between Islam and her ideas. She is considered a humanist, secular writer of great stature and the ‘grande dame’ of British writing of her time, and she handles explicit sexual relationships especially in The Golden Notebook (1962). Hence, a sense of remoteness and incomprehension is, perhaps, palpable in any attempt to establish profound affinities between Islam and this Nobel laureate, or to dare to discover an ‘Islamic Doris Lessing’. However, given her reputation as an author known for her courage and outspokenness and for making unconventional moves and iconoclastic statements sometimes at the expense of her reputation as a formidable literary talent, it will be interesting to see how Islam views her ideas on some specific issues. It is in this spirit that, in this paper I will explore how Lessing’s views on education, literature, racism and women’s rights can be discussed in a classroom setting in line with the Islamization and integration of knowledge undertaking at such an Islamic university as International Islamic University Malaysia.